Management of Biomedical Waste in Hospital and Health Care Organizations- A Review - Shruti Sinha1 , N.Aravindha Babu2 , Shyam Sundar Behura3 , E.Rajesh4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Bio-Medical Waste (BMW) is a global concern. In common parlance BMW means any waste generatedin the process of diagnosis, treatment, immunization and research related to human beings and animals.Due to improper or poor waste management practicesa huge risk is posed to the health of public, patients,professionals and also cause environmental disturbance. The Union Ministry of Environment and Forestsunder the provision of Environment [protection] act, 1986 which brought the focus back on this issue. Theserules apply to all the people who are connected to generation, collection, receiving, storage, transportationand handling or biomedical waste in any form. This article aims to highlight the categories, segregation andmanagement protocols by various government and non- government organizations and spread knowledgeabout the same